Mental health in university students: exploring the influence of family communication and age on youth suicide risk (2026)
Background Suicide accounts for 1 in every 100 deaths, which sets it as a global public health concern per the World Health Organization. COVID-19 increased concerns about mental health, particularly among youth, with suicide ranking as the fourth leading cause of death. This study investigates the relationship of age and the quality of family communication on suicidal ideation among Colombian university students, thus addressing a pertinent issue as Colombia reports an average of 8 daily suicide deaths. Methods A cross-sectional correlational design was employed, involving a representative sample of 660 Colombian university students aged between 18 and 26 years old. The study employed the Positive and Negative Suicide Ideation Inventory and the Parent–Adolescent Communication Scale. Participants were categorized into two groups: those surveyed before and during the COVID-19 pandemic. Results During the pandemic family communication, particularly of an offensive nature, had a significant relationship on suicidal ideation among young Colombian university students. A positive association was found between the pandemic context and suicidal ideation, moderated by age. Open family communication was observed to potentially mitigate suicidal thoughts, particularly among older students. Conclusion This research highlights the role of family communication in supporting students’ mental health during crises like the COVID-19. Future studies should explore the preventive potential of close interpersonal communication to reduce youth suicide risk. Implementing proactive measures and robust support systems within universities are essential for approaching this issue and protecting vulnerable youth. Additionally, considering individual developmental trajectories is relevant for understanding age-related influences on student mental health.